DNA Damage, Glutathione, and Total Antioxidant Capacity in Anesthesia Nurses - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
The possibilities of a potential mutagenic/carcinogenic action of waste anesthetic gases in occupationally exposed anesthesia personnel have been previously reported in several studies. The aim of this study was to assess the DNA damage, reduced glutathione (GSH), and total antioxidant capacity (TAC) in anesthesia nurses. DNA damage was determined with comet assay, GSH levels were measured spectrophotometrically, and TAC was determined by using Randox kit. Anesthesia nurses (n = 40) showed increased DNA damage in terms of mean percentage of the total DNA in the comet tail compared to controls (n = 40) (p < .001). Mean TAC and GSH levels of the anesthesia nurses were significantly lower than that of the controls (p < .001, p < .05, respectively). The results of this study indicate that occupational exposure to anesthetic gases induce DNA damage, which may lead to changes in TAC and GSH levels.
Keywords: DNA damage; glutathione levels; total antioxidant capacity; waste anesthetic gases; SISTER-CHROMATID EXCHANGES; OPERATING-ROOM PERSONNEL; COMET ASSAY; OCCUPATIONAL-EXPOSURE; VITAMIN-E; CIGARETTE-SMOKING; PERIPHERAL-BLOOD; OXIDATIVE STRESS; S-TRANSFERASES; GENETIC-DAMAGE